Depositional architecture and peculiar sedimentary features of late Cretaceous Utrillas Formation at Tamajón (Guadalajara, Spain) - García-Hidalgo, José F.; Gil-Gil, J.; Segura, M.; Carenas, B. (Journal of Iberian Geology, 2016)
The Utrillas Formation represents clastic wedges that accumulated in relation to continental-coastal areas of Iberian Basin during the worldwide late Cretaceous sea-level rise. At the Tamajón outcrop the late Cenomanian Utrillas wedges are composed of four facies associations (FA1 to FA4), which unconformable overlay Triassic deposits. Basal sediments (FA1) are interpreted as high energy, braided fluvial deposits, characterized by coarse-grained (conglomerate–sandstone) facies; which grade upwards to tide-influenced, estuarine sedimentation (sandstones and mudstones with inclined heterolithic stratification, FA2), and then to high-energy, coastal sheet and channelled sandstones with different tidal features (FA3); and finally, to fine-grained (mudstones and minor burrowed sandstones) of an offshore marine associations (FA4). The depositional architecture based in the presence and hierarchy of several ranks of bounding surfaces and the overall upward-fining succession show the long term retrogradational trend of these facies associations. Peculiar sedimentary features of these sediments are 1) the presence of large-scale, single sets of cross beds infilling large erosive channels, which are tidal (not aeolian) in origin. 2) The size and length of the cross-bedding defined by couplets of different grain size; here interpreted as originated by flow unsteadiness in relation to changing tides. And 3) an unusual association of ironstones, wrinkle structures and vertebrate tracks with microbial mats and penecontemporaneous iron encrusting allowing track preservation in the sedimentary record.
Keywords: continental-coastal facies; large-scale channels; ferruginous crusts; wrinkle marks; vertebrate tracks; Cenomanian.